(untitled) (Journal of Engineering, 2009)
This paper describes two new developed detection processes for a modem over the public switched telephone network. The modem is a synchronous serial system using a 16-point QAM signal with a detector. The detector is preceded by an adaptive filter that is adjusted to make the sampled impulse response of the channel and filter minimum phase. The idea of these two new detectors is to transmit a known retraining data every specified interval and make use of these known data to improve the conventional nonlinear equalizer and near maximum likelihood detector. Results of computer simulation tests are presented comparing tolerance to additive white Gaussian noise with retraining and with out retraining. The detectors with retraining achieve a better noise performance than conventional detectors. Furthermore the amount of retraining data is varied to find the best compromise between efficiency of data transmission and performance improvement